Toward a Constructive Discourse on “Christology of Tuak-Tempayan” - Nyaming, Fransiskus Gregorius; Watu, Christianus (Studia Philosophica et Theologica, 2025)
This article aims to respond to an article titled " Christology of Tuak-Tempayan," published in the Journal Studia Philosophica et Theologica Vol. 24, No. 2, 2024. Drawing from pastoral experience in the Nanga Mahap Parish, Sanggau Diocese, the author of the article aims to help Catholics understand the mystery of the Second Person of the Holy Trinity, who is truly God and truly man. He uses the phenomenon of distilling palm wine in clay pots as a means to understand and explain the mystery of faith to the faithful. In providing a response, this article uses the qualitative method of literature study. The results of this response indicate that the cultural elements chosen to understand and explain the Christological dogma are less suitable and appropriate for use. This article also shows that the concept of "Tuak-Tempayan Christology" to some extent does not heed the Church's teachings, especially regarding theology and the interpretation of dogma closely related to the communion of the Church. In order for "Tuak-Tempayan Christology" to truly become a contextual christology, this article suggests that reflections on the phenomenonof tuak-tempayan be linked to the life experiences of the Dayak people and the cries of the earth where they live.